Removal of Methylene Chloride from Paint Stripping Waste water by Air Stripping Process - Lim, Poh Eng (Universiti Putra Malaysia Press, 1996)
Laboratory-scale air stripping experiments were conducted at various unit air flow rates (Q) to remove methylene chloride from paint stripping waste water. The results showed that the removal of methylene chloride by batch diffused air stripping process follows first-order kinetics and that the concentration of methylene chloride could be reduced to less than 0.1 mg I-I within 120 min at a unit air flow rate of 0.833 1 min-II-I. The stripping rate constant k , which quantifies the rate of air stripping, can be predicted from the equation k = (H/RT) Q; where H is the Henry's law constant, R a universal constant and T temperature, provided that Qis kept within 0.833 1min-I I-I. The values of k were found to be 0.028,0.056,0.088 and 0.087 min-I at Q of 0.286, 0.571, 0.833 and 1.33 1 min 1-1, respectively.